Passing and goal scoring characteristics in Australian A-League football - Garratt, K.; Murphy, A.; Bower, R. (International Journal of Performance Analysis in Sport, 2017)
The aim of this study was to analyse passing sequences, shots and goals in elite Australian football (soccer). Using a computerised video analysis system (Sportsdata Pty Ltd©), notated data relating to the number of passes per possession were collected from 84 A-League matches. A total of 36,297 possessions were analysed, resulting in 220 goals. The results indicate that a higher proportion of goals were scored from longer passing sequences (five or more passes), producing an average of 13 goals per 1000 possessions compared to 6 goals per 1000 possessions from shorter passing sequences (four or less passes). Notably, 46% of team possessions were zero length passing possessions compared to approximately 25% reported in existing literature. In order to improve team possession and goal scoring efficiency, it is recommended that A-League coaches implement programmes designed to enhance individual skills and develop effective team strategies.